Essentials of pharmacology for health professions - Ruth Woodrow; Bruce J. Colbert (Boston, Massachusetts : Cengage, 2019)
Best-selling ESSENTIALS OF PHARMACOLOGY FOR HEALTH PROFESSIONS, 8e is the ideal resource to help you prepare for licensed practical nursing, medical assisting, and other allied health careers. Focusing on "need to know" drug information, it gives you the confidence to master pharmacology. Extremely reader friendly, this clear, concise book simplifies material into engaging and manageable chapters. By stressing clinical application, it also ensures you understand the "why" behind what you learn. Part I provides a solid foundation in basic pharmacologic principles. Part II covers drugs, sources, legal concerns, and medical uses. Chapters organize drugs by classifications and include their purpose, side effects, interactions, and precautions or contraindications. Patient education is highlighted for each category, while numerous reference tables help pull everything together for you by listing the most commonly prescribed drugs, dosages, available forms, and special considerations
Keywords: Allied Health Occupations; Chemotherapy; Pharmacology Examinations, questions, etc; Pharmacological Phenomena